2015
DOI: 10.1177/0022146514568350
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Contexts

Abstract: We use data from the National Longitudinal Survey of Adolescent Health (13,186 respondents in 30 states) to develop a unique state-level measure of the gendered context, in order to examine the influence of gender normative attitudes and behaviors on state rates of suicidal ideation and individual-level suicidal ideation for female and male youth (aged 13 to 22). The findings demonstrate the negative consequences for youth, especially females who report feminine-typical traits, who live in contexts defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…Moreover, this study found that the proportions of suicidal ideation and suicide attempts were respectively 17.4 and 5.7% among US adolescents, which were higher than those among Chinese adolescents (suicidal ideation: 13.7% and suicide attempts: 2.7%); these results were consistent with previous studies ( 31 , 32 ). In line with prior studies ( 32 ), we found that in females, being bullied, feeling sad, cigarette use, alcohol use, and prescription pain medication use were positively associated with suicidal ideation and suicide attempts.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, this study found that the proportions of suicidal ideation and suicide attempts were respectively 17.4 and 5.7% among US adolescents, which were higher than those among Chinese adolescents (suicidal ideation: 13.7% and suicide attempts: 2.7%); these results were consistent with previous studies ( 31 , 32 ). In line with prior studies ( 32 ), we found that in females, being bullied, feeling sad, cigarette use, alcohol use, and prescription pain medication use were positively associated with suicidal ideation and suicide attempts.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the small number of male respondents, this may not be representative of the larger population. However, evidence has shown that adolescent and adult females report a higher percentage of suicidal ideations compared with their male counterparts [ 16 , 17 ]. A full-scale intervention evaluation examining high-risk responses is required to suggest gender differences among Ohio adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This approach represents a different method of measuring gender compared with scales such as the Bem Sex Role Inventory, 24 for which the questions remain the same over time. The gender expression measure was developed by Cleveland and colleagues 23 to examine genetic differences in gender-related behaviours, applied by Nowotny and colleagues 25 to evaluate the association between gendered behaviours and suicidal ideation, and further refined and applied by Fleming and colleagues 22 to analysis of violent behaviour and substance use 20 . The gender expression measure is calculated with behaviours and attitudes considered typical of individuals of a given sex and a given age and time period.…”
Section: Introductionmentioning
confidence: 99%